2012
DOI: 10.15835/nbha4027987
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Arbutin and Hydroquinone in Different Plant Materials by HPLC

Abstract: A simple, fast method of high-performance liquid chromatography for the determination and quantification of arbutin and hydroquinone in many different raw materials was developed and validated. The optimum conditions for the separation and detection of these two constituents were achieved on a LiChro-CARD 125-4 Superspher®100 RP-18 column with the water-methanol (gradient elution) mobile phase and recorded at 289 nm. The purities of peaks were verified by PDA analysis of impurities. The results of validation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 10 publications
3
21
0
11
Order By: Relevance
“…Table 1 shows the LOD, LOQ, and precision of the developed method as well as the analytical recovery of the studied compounds. The precision of the method (RSD<5 %) and analytical recovery (96.2-98.0 %) were comparable to the previously developed HPLC methods for arbutin and hydroquinone quantification in leaf extracts (17,18) or arbutin quantification in medicinal plant extracts (24) as well as to the GC-MS method for arbutin quantification in leaf extracts (20). The LOD for arbutin (0.009 µg mL -1 ) and for hydroquinone (0.004 µg mL -1 ) obtained in this study showed an improvement in method sensitivity over the HPLC methods reported by Fecka and Turek (17) and Rychlinska and Nowak (18) (LODs>0.49 µg mL -1 ) and the GC-MS method reported by Lamien-Meda et al (20) (LOD for arbutin=0.13 µg mL -1 ).…”
Section: Analytical Features Of the Proposed Gc-ms Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…Table 1 shows the LOD, LOQ, and precision of the developed method as well as the analytical recovery of the studied compounds. The precision of the method (RSD<5 %) and analytical recovery (96.2-98.0 %) were comparable to the previously developed HPLC methods for arbutin and hydroquinone quantification in leaf extracts (17,18) or arbutin quantification in medicinal plant extracts (24) as well as to the GC-MS method for arbutin quantification in leaf extracts (20). The LOD for arbutin (0.009 µg mL -1 ) and for hydroquinone (0.004 µg mL -1 ) obtained in this study showed an improvement in method sensitivity over the HPLC methods reported by Fecka and Turek (17) and Rychlinska and Nowak (18) (LODs>0.49 µg mL -1 ) and the GC-MS method reported by Lamien-Meda et al (20) (LOD for arbutin=0.13 µg mL -1 ).…”
Section: Analytical Features Of the Proposed Gc-ms Methodssupporting
confidence: 66%
“…Since hydroquinone was not detected in the leaf samples, a standard solution of hydroquinone in methanol was added to samples to contain 1 mg g -1 dried weight to optimise the extraction procedure. This concentration was chosen according to the literature data regarding hydroquinone content in the leaves of Arctostaphylos uva-ursi, Vaccinium vitis-idaea, and Origanum majorana (17,18). Arbutin and hydroquinone were extracted from samples with 5 or 15 mL of methanol, 80 % methanol, ethyl acetate, and dichloromethane using Jurica …”
Section: Optimisation Of the Extraction Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the absorbance is observed near 250 nm and can be attributed to the formation of intermediates, especially benzoquinones. In addition, the absorption spectrum displays a bathochromic shift towards 285 nm, indicating the formation of intermediary species with a different cromophore group, such as hydroquinone . This last peak (285 nm), assigned to the n → π * transitions of C–Cl bond, decreases rapidly because this bond is the most reactive.…”
Section: Resultsmentioning
confidence: 97%
“…So far, several studies reported on the determination of 1 and the other hydroquinones in different plant materials (Rychlińska & Nowak 2012), and 2 in sunflower seeds (Aramendía et al 2000) by HPLC methods. However, none of them are applicable to the simultaneous analysis of 1-3.…”
Section: Introductionmentioning
confidence: 99%